The Emergent Literacy Activities Through the Storytelling Method with Flashcard Media for Early Childhood Education - Dani Puspitasari; Bella Vania Lim; Ribka Evelina; Yulia Setia (MO.RI Publishing, 2023)
Teachers have an important role in the development of children's language at school. The study period at Early Childhood Education is an excellent opportunity to improve literacy skills when children are experiencing a sensitive language learning period. Language skills have a role in improving social aspects and developing emotional and cognitive aspects. Children aged 2-4 years go through a concrete learning period. Using storytelling teaching methods with flashcard media can create a fun learning atmosphere and encourage children to learn optimally. This study aims to look at the application of the flashcard storytelling method to the language skills of children aged 2-4 years in support of an emergent literacy program.